2022
DOI: 10.1021/acsami.2c04931
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance and Rapid-Response Electrical Heaters Derived from Cellulose Nanofiber/Silver Nanowire Nanopapers for Portable Thermal Management

Abstract: High-performance electrical heaters with outstanding flexibility, superior portability, and mechanical properties are highly desirable for portable thermal management. However, it is still a huge challenge to simultaneously achieve competent electrical heating performances and excellent mechanical properties. Herein, inspired by the Janus structure, versatile electrical heaters are developed via a sequential assembly followed by a hot-pressing strategy. The elaborately designed Janus structure is composed of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The ULCuNWs40/ANF nanopapers treated at 180 °C, for example, show λ // as high as 16.32 W·m –1 ·K –1 , resulting in an increase of 32% and 49% in comparison to that of the ULCuNWs40/ANF nanopapers with thermal treatment at 100 °C and no thermal treatment, respectively. The higher λ // after thermal treatment could be because the ULCuNWs are merged at the intersection owing to the removal of the organic layer on the ULCuNWs surface at high temperatures, which is demonstrated by previous literature . Since the alignment of 1D ULCuNWs invariably results in anisotropy in the thermal conductivity, the through-plane thermal conductivity λ ⊥ of the ULCuNWs/ANF nanopapers was also investigated, as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The ULCuNWs40/ANF nanopapers treated at 180 °C, for example, show λ // as high as 16.32 W·m –1 ·K –1 , resulting in an increase of 32% and 49% in comparison to that of the ULCuNWs40/ANF nanopapers with thermal treatment at 100 °C and no thermal treatment, respectively. The higher λ // after thermal treatment could be because the ULCuNWs are merged at the intersection owing to the removal of the organic layer on the ULCuNWs surface at high temperatures, which is demonstrated by previous literature . Since the alignment of 1D ULCuNWs invariably results in anisotropy in the thermal conductivity, the through-plane thermal conductivity λ ⊥ of the ULCuNWs/ANF nanopapers was also investigated, as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 80%
“…The higher λ // after thermal treatment could be because the ULCuNWs are merged at the intersection owing to the removal of the organic layer on the ULCuNWs surface at high temperatures, which is demonstrated by previous literature. 15 Since the alignment of 1D ULCuNWs invariably results in anisotropy in the thermal conductivity, the throughplane thermal conductivity λ ⊥ of the ULCuNWs/ANF nanopapers was also investigated, as shown in Figure S2. It is evident that the λ ⊥ of the ULCuNWs/ANF nanopapers also shows an increase with an increase in the weight fraction of the ULCuNWs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9a †), corresponding to the theoretical prediction model. 81,82 These results conrm that the device possesses huge potential in heating systems with intelligently adjustable temperature. The heating recyclability and stability of the device were evaluated by 50 on-off cycles at 5 V. As shown in Fig.…”
Section: Snf/mxene Composite Aerogels As a Dmtm Devicementioning
confidence: 93%
“…Wearable electronic heaters are another important subfield of wearable electronics due to their potential application in personal healthcare, thermotherapy, heat preservation in textile or clothing, and athletic rehabilitation. Heaters based on Joule heating attracts great attention in the thermotherapy for relieving pain and revitalizing muscles of injured skin/joints/tissues. , In theory, the Joule heater and resistive-type strain sensor have similar structures mainly consisting of a functional conductive layer and substrate layer. , Thus, it is promising to integrate the Joule heater and strain sensor in one wearable electronic device. However, most resistance-type strain sensors exhibit a positive resistance variation during human motion monition; in other words, the electrical resistance of strain sensor increases with the increase of strain due to the fraction of the continuous conductive network. Although this type of strain sensors demonstrates a high relative resistance change, good gauge factor, and excellent sensitivity, it is problematic to serve as a Joule heater because the increase of resistance results in the decrease of heating temperature according to Joule’s rule ( Q = U 2 t / R , where Q is heat energy, U is applied constant voltage, t is time, and R is resistance) . Therefore, few studies on combining wearable strain sensors and Joule heating have been reported. Their strain-imposed thermal stabilities were usually poor, and the Joule heating temperature considerably decreased during stretching. So, it is still a big challenge to integrate the strain sensor and heater into one device.…”
Section: Introductionmentioning
confidence: 99%